1H–31P HETCOR NMR elucidates the nature of acid sites in zeolite HZSM-5 probed with trimethylphosphine oxide. Issue 84 (3rd October 2019) - Bornes, Carlos; Sardo, Mariana; Lin, Zhi; Amelse, Jeffrey; Fernandes, Auguste; Ribeiro, Maria Filipa; Geraldes, Carlos; Rocha, João; Mafra, Luís
Abstract : 2D 1 H– 31 P NMR and DFT calculations extend the understanding of TMPO:Brønsted complexes formed at HZSM-5 zeolite surfaces, providing structural insight into the proton-transfer mechanism. Abstract : Two-dimensional 1 H– 31 P heteronuclear correlation NMR of trimethylphosphine oxide (TMPO) adsorbed in zeolites, in tandem with DFT calculations, challenges previous one-dimensional 31 P NMR assignments, enabling the unambiguous discrimination of Brønsted and Lewis acid sites, extending the understanding of TMPO:Brønsted complexes formed with distinct stoichiometries at the HZSM-5 zeolite surface, and the proton-transfer mechanism.